Impact of electrically activated water fractions on functional and processing properties of beef and pork - Віннікова, Людмила Григорівна; Пронькіна, Ксенія Володимирівна (Eastern-European Journal of Enterprise Technologies, 2015)
The article shows the influence of electrically activated water on functional and processing properties of beef and pork. It determines the dependence of pH, water-binding capacity, and losses during heating of test items on induced mixture of electrically activated water fractions. The article establishes that using electrically activated water fractions within ratio range of 30/70 – 100 % catholyte allows to purposefully change the active acidity of minced beef and pork; to change water-binding capacity of beef from 1 % to 8 %, of pork – from 0.7 % to 8.8 %; decrease water loss from heating for beef on 1.6–8.6 %, for pork – from 1.8 to 8.8 %. The author points out the practical importance of electrically activated water in production of cooked sausage. The article describes the influence of electrically activated water on organoleptic properties of test items. Positive quality attributes of items with electrically activated water fractions were observed within catholyte/anolyte fraction ratio range of 70/30 – 40/60. Their quality attributes are most stable in the storage process. The article determines the most effective ratio of electrically activated water fractions for improvement of beef and pork properties. It is recommended to use electrically activated water with catholyte/anolyte fraction ratio range of 70/30 in the amount of 20–25 % to the mass of meat.